2016
DOI: 10.1016/j.nwh.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of the Childbearing Cycle as Experienced by Survivors of Sexual Abuse

Abstract: For women who have experienced sexual abuse, the physical changes associated with pregnancy and the lack of control during birth can be catalysts for trauma from past abuse to resurface. This systematic review offers women's health care providers a thorough evaluation of the state of the science on survivors' childbearing experiences. The literature shows that lack of control, dissociation, and flashbacks are common themes. Re-experiencing of the trauma occurred during various stages of childbirth and was trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…forceps, vacuum extraction or cesarean section [84], while a recent study found that women who were sexually or physically abused in childhood had a higher level of fear of childbirth and were more likely to experience a complicated vaginal birth. Specifically, women raped in childhood had a considerable greater risk for C-section (OR 15.7, 95% CI 5.0-49.1) or assisted vaginal birth (OR 13.1, 95% CI 4.9-34.5) [85] or more difficult pregnancies and delivery [86]. It is difficult to explain this unexpected result; however, it may be related to the high proportion of planned C-section among abused women [87], perhaps due to worry about their infant's health [88].…”
Section: Pregnancy Motherhoodmentioning
confidence: 99%
“…forceps, vacuum extraction or cesarean section [84], while a recent study found that women who were sexually or physically abused in childhood had a higher level of fear of childbirth and were more likely to experience a complicated vaginal birth. Specifically, women raped in childhood had a considerable greater risk for C-section (OR 15.7, 95% CI 5.0-49.1) or assisted vaginal birth (OR 13.1, 95% CI 4.9-34.5) [85] or more difficult pregnancies and delivery [86]. It is difficult to explain this unexpected result; however, it may be related to the high proportion of planned C-section among abused women [87], perhaps due to worry about their infant's health [88].…”
Section: Pregnancy Motherhoodmentioning
confidence: 99%
“…Prior mental health disorders and poor quality of provider interaction are risk factors for birth trauma (Simpson & Catling, 2016). Women who are survivors of sexual abuse are at risk for retraumatization during childbearing (LoGiudice, 2016).…”
mentioning
confidence: 99%
“…30,31,33–35 Several suggestions for offering supportive and trauma-informed care during the labor and birth process include offering detailed explanations for physical examinations and procedures, insisting on clear verbal consent, and allowing for examinations to stop or pause at any time. 30,31,33–35…”
Section: Discussionmentioning
confidence: 99%